FACTORS INFLUENCING WILLINGNESS TO COMMUNICATE IN A COMMUNITY COLLEGE ESL CLASSROOM - Wirdawati Ahmad @ Mohd Isa; Muhammad Fairuz Jamil; Siti Nurhazirah Lidon (Journal of Islamic, Social, Economics and Development, 2022)
The purpose of this research is to investigate the situational factors that influenceMalaysian community college students’ willingness to communicate (WTC). A quantitativeresearch design was adopted to obtain data from 53 respondents in three different academiccourses’ answers to the questionnaire. The analysis of the data using SPSS for the mean offrequency shows that the participants were moderate in WTC levels and that teachers, peers,topic preferences, types of activities, and seating location are the factors influencing WTC.Therefore, a variety of variables influence students' WTC and avoid assuming that someone'sWTC is influenced only by one factor.